2017
DOI: 10.4236/jacen.2017.63009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liquid Pig Manure and Chemical Fertilizers on Shoot Growth and Nitrogen Status of Young “Fuyu” Persimmon Trees

Abstract: Liquid pig manure (LPM), digested from pig slurry, has been used as a nutrient source substituting chemical fertilizer (CF) for some crops. This experiment was conducted to evaluate the effect of different levels of CF and LPM in early July on nitrogen (N) uptake of pot-grown young "Fuyu" persimmon (Diospyros kaki). The total N and potassium (K) from CF and LPM applied to a 3 L pot were 1.2 g N and 1.15 g K for the low and 2.4 g N and 2.3 g K for the high level. From 2 weeks after the applications, secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The LPM has widely been applied in rice paddy as a basal fertilizer (Hong et al, 2010;Jeon et al, 2003) in Korea. Also in horticultural crops including fruit trees, previous studies have confirmed there was no difference in growth and quality of the crops between chemical fertilizer and LPM when they were properly applied (Lim et al, 2008;Lim et al, 2009;Park et al, 2012;Lee and Seong, 2015;Choi et al, 2017). Some persimmon growers have tried the LPM but it has not yet been widely used in the orchards due to several difficulties including little information about effects of the LPM.…”
Section: Research Articlementioning
confidence: 99%
“…The LPM has widely been applied in rice paddy as a basal fertilizer (Hong et al, 2010;Jeon et al, 2003) in Korea. Also in horticultural crops including fruit trees, previous studies have confirmed there was no difference in growth and quality of the crops between chemical fertilizer and LPM when they were properly applied (Lim et al, 2008;Lim et al, 2009;Park et al, 2012;Lee and Seong, 2015;Choi et al, 2017). Some persimmon growers have tried the LPM but it has not yet been widely used in the orchards due to several difficulties including little information about effects of the LPM.…”
Section: Research Articlementioning
confidence: 99%
“…The simultaneous application of organic fertilizers and CFs could increase soil moisture, improve soil organic matter content, maintain soil nutrient balance, and increase crop yields (Abbasi et al., 2013). Manure is important in providing nutrient supplies because it contains nutrients necessary for the production of many crops (Choudhary et al., 1996; Choi et al., 2017; Kim et al., 2013). For instance, cow ( Bos taurus ) and chicken ( Gallus domesticus ) manure returned to the field increased the N content and its uptake of N by cocksfoot ( Dactylis glomerata L.); moreover, the best results were obtained after the application of chicken manure (Kuziemska et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…LM are therefore, organic fertilizers formed by mixing and dissolving factory waste, crop residues, urine, green manures, sawdust, market waste, animal dung, household/kitchen waste, mushroom waste, agro-industrial wastes and farm residues, among othersby way of fermenting and/or decomposing them (Ansar et al, 2021;Elaiyaraju & Partha, 2016;Rana, n.d.;Supriya & Harish, 2019). In various farmlands, the efficiency of LM in growing certain types of crops compared to chemical fertilizers, has been studied with near 100% success by many researchers (Alamene & Howells, 2022;Antoneli et al, 2019;Arunkumar et al, 2021;Byeon et al, 2021;Choi et al, 2017;Gajjela et al, 2018;Msibi et al, 2014). In whatever form (solid, semi-solid or liquid form), manures have the potential of polluting water bodies and the surrounding air, by causing GHG emissions, ground water pollution, leaching of pollutants, soil salinization and eutrophication of surface water (Ahlberg-Eliasson et al, 2021;Antoneli et al, 2019;Camilleri-Rumbau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%